Research on Teaching Strategies of Oral Communication in Elementary School Language - Shi, Shuai (Cultural and religious studies, 2022)
In the context of continuous social progress, the forms of communication between people have become frequent and diverse, and good oral communication skills and standardized oral communication habits are especially important. Oral communication skills are not only an important reflection of one’s overall quality, but also concern one’s development and future. Teachers should seize this opportunity to provide targeted oral communication training to elementary school students, encourage them to express themselves and communicate with others actively, and develop their oral communication skills in the process.